Bearing Capacity of Galam Wooden Foundation on Soft Soil and Peat in Kalimantan Tengah - Silaban, Ridho Saleh (Fakultas Teknik Universitas Tanjungpura, 2024)
Many structures in Central Kalimantan are built on soft soil and peat. One type of foundation that can be used for support is the Galam wooden foundation. To ensure stability, the required number of Galam wooden piles must be calculated based on the working load. The foundation